PENGARUH PEMBERIAN REBUSAN DAUN ALPUKAT (PERSEA AMERICANA MILL) TERHADAP PENURUNAN TEKANAN DARAH PASIEN HIPERTENSI PRIMER DI WILAYAH KERJA PUSKESMAS NANGGALO - Febriyanti, Viki Yusri, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Padang City Health Office, 2017 the number of hypertension 6392 cases, and in 2018 hypertension to the top position of 6714 cases. The impact of high blood pressure results in damage to blood vessels, kidneys and eyes. One way to control blood pressure with non-pharmacological therapy is to use avocado. This study aims to see the effect of decoction of avocado leaf (persea americana mill) to decrease blood pressure of hypertensive patients in the work area of Nanggalo Puskesmas Padang. The type of research used is pre-experiment with One Group pre-post design. Population of all patients with hypertension as many as 57 people with sampling technique purposive sampling which amounted to 10 people. The result of univariate analysis showed that the average blood pressure of hypertension patient before was given avocado leaf stew was 164/94 mmHg and after given avocado leaf stew (persea americana mill) was 156,40 / 86,50 mmHg. There is the effect of decoction of avocado leaves (persea americana mill) to the decrease in blood pressure of hypertensive patients. It was concluded that there was an effect of avocado leaf stew (persea americana mill) to the decrease in blood pressure of hypertensive patients.Keywords : Avocado Decoction, Blood Pressure, Hypertension